Analisis Strategi Pemasaran Media Sosial, Kepuasan Pelanggan, dan Rekomendasi Pelanggan dalam Membangun Loyalitas Milenial (Studi Pada Produk BSI Cicil Emas) : Penelitian - Putri Nur Syafitri Lubis; Onan Marakali Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to analyze the social media marketing strategies implemented by BSI for the gold installment product, as well as to analyze the role of customer satisfaction and customer recommendations in building loyalty among millennial customers. The research method used is qualitative with a descriptive approach. The data sources consist of primary and secondary data, collected through observations, interviews, and documentation. The informant selection technique employs snowball sampling, which allows the researcher to gradually expand the number of informants. Data analysis is conducted using the Miles and Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that BSI has successfully implemented an effective social media marketing strategy for Cicil Emas products. By utilizing platforms such as Instagram and WhatsApp, BSI is able to create a positive experience for millennial customers. In addition, high customer satisfaction contributes to customer loyalty, where recommendations from satisfied customers become a powerful marketing tool. However, there is still room for improvement regarding inform